2001
DOI: 10.1046/j.1365-2281.2001.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of airway conductance and FEV1 as measures of airway responsiveness to methacholine

Abstract: When defining bronchial responsiveness in healthy, non-asthmatic, subjects exposed in different working situations, it is not clear whether different outcome measures yield similar results. Therefore, the concentration and dose of methacholine that caused a 20% decrease in forced expiratory volume in 1 s (FEV(1)) (PC20(FEV(1)) and PD20(FEV(1))), the corresponding change in Gaw and the relationship between the dose-response slope (DRS) for FEV(1) and Gaw was studied in different working populations and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Discordance between measurements of SGaw and FEV 1 could theoretically result from several factors. Deep inspiration can reduce bronchoconstriction provoked by nonspecific stimuli in healthy individuals and in asthmatic subjects with mild to moderate bronchial hyperresponsiveness, whereas it can enhance induced bronchoconstriction in asthmatics with marked hyperresponsiveness (9–11, 21). In addition, it has been postulated that SGaw and FEV 1 assess different portions of the airways, with SGaw reflecting primarily the flow‐resistive properties of large, central airways (22, 23), although this concept has been subsequently questioned (24).…”
Section: Discussionmentioning
confidence: 99%
“…Discordance between measurements of SGaw and FEV 1 could theoretically result from several factors. Deep inspiration can reduce bronchoconstriction provoked by nonspecific stimuli in healthy individuals and in asthmatic subjects with mild to moderate bronchial hyperresponsiveness, whereas it can enhance induced bronchoconstriction in asthmatics with marked hyperresponsiveness (9–11, 21). In addition, it has been postulated that SGaw and FEV 1 assess different portions of the airways, with SGaw reflecting primarily the flow‐resistive properties of large, central airways (22, 23), although this concept has been subsequently questioned (24).…”
Section: Discussionmentioning
confidence: 99%
“…This may be underestimated in individuals with elevated TLC. The provocative concentration of methacholine causing a 20% fall in FEV1 (PC 20 ) has also been described by several investigators as being a useful marker of air trapping [25], while greater sensitivity has been reported when both FEF 25-75 and FEV1 were used together to evaluate the response to methacholine. Finally, the difference between slow inspiratory vital capacity (SVC) and FVC and the FVC to SVC ratio may be surrogate markers of the collapsibility of small airways [26].…”
Section: Assessment and Monitoring Of Small Airways Diseasementioning
confidence: 99%
“…In adults, Sundblad and colleagues have shown that a 20% change in FEV 1 following methacholine corresponds to different levels of change of G aw (reciprocal of R int ) determined by the interrupter technique, depending on the underlying degree of bronchial responsiveness, in this case, to a 39% change in G aw in all subjects, but a 66% change in less responsive subjects and a 27% change in more responsive subjects. 75 Thus, the range of cutoff of a positive test varies widely, depending on the nature of the underlying bronchial responsiveness.…”
Section: Measurement Of Airway Resistance By the Interrupter Techniquementioning
confidence: 99%